Active isolation tests of metamaterial-based barriers and foundation. (1st June 2022) - Wang, Jiaji; Huang, Hsuan Wen; Zhang, Benchen; Menq, F.-Y.; Nakshatrala, Kalyana Babu; Mo, Y.L.; Stokoe, K.H.
Highlights: Active-isolation field tests for with empty trenches, periodic barriers and periodic foundations. A state-of-the-art shaker truck is used to apply triaxial excitation on superstructure. Triaxial soil responses and structure responses are reported in detail. Metamaterial's performance are dependent on the frequency and direction of excitation. The attenuation zone is identified experimentally and well agree with theoretical frequency band gap. Abstract: This study investigates the performance of novel metamaterial-based barriers and foundation on mitigating waves transmitting from a vibrational source to the surrounding soil. An active isolation system is a wave barrier built close to the vibration source to reduce the wave radiating from the source of vibration on the structure to surrounding soil. This research reports the efficacy of the proposed isolation system using an active excitation field test, thereby expanding the applicability of such wave barriers beyond passive isolation. The test barrier is a trench barrier infilled with a layered periodic metamaterial that is composed of alternating layers of polyurethane and reinforced concrete (RC). Tests are also conducted on an empty trench for comparison. A mobile shaker mounted on top of a steel frame is utilized to simulate an active vibration source. By mechanically reorienting the shaker, active isolation tests can be conducted in all three directions (vertical, horizontal inline, and horizontal crossline). Motions on the ground surface, periodic barrier, foundation, and steel frame are monitored using three-dimensional (3D) geophones and 3D accelerometers. The effects of the barrier length, the infilled material, and the total number of barriers on the isolation behavior at various exciting frequencies, and excitation directions are investigated. Tests also include the scenario where the wave barrier is used along with a metamaterial-based periodic foundation. Experimental studies show that vibrations generated from the shaker mounted on top of the steel frame are effectively restrained by a metamaterial-based foundation. The performance of the periodic barriers is better than that of an empty trench within certain frequency ranges. The wave isolation performance is enhanced with the increasing barrier length. This research provides the benchmark for the future design of periodic barriers and periodic foundations in buildings or other vibration-sensitive facilities.